Kajian Lighting Patterns Pada Karya Fotografi Model Pameran Kirana Dakara 2021 - Rezki Gautama Tanrere (ULTIMART Jurnal Komunikasi Visual, 2021)
Lighting patterns is a technique of lighting settings in portrait photography that pays attention to the shapes of light and shadow on the subject's face, in general a model. This lighting patterns technique are applied on the photographic works at Kirana Dakara 2021 exhibition, an exhibition by students from Advanced Photography course in the Visual Communication Design study program, Multimedia Nusantara University, held at Dharma Negara Alaya, Denpasar, Bali. The results of this research conducted indicate that the use of various types of lighting patterns has different roles and functions. By choosing the right lighting patterns, each photo works can give a message and impression that is in accordance with the concept and theme that the photographer wants to achieve. As a result, the use of various types of lighting patterns in the photographic works exhibited at Kirana Dakara 2021 can be a powerful visual medium in introducing the legendary characters of the Indonesian archipelago. Keywords: lighting patterns; model photography; photography exhibition